2000
DOI: 10.1200/jco.2000.18.13.2560
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy for Breast Cancer: A Suitable Alternative to Routine Axillary Dissection in Multi-Institutional Practice When Optimal Technique Is Used

Abstract: In multi-institutional practice, SLN biopsy using dual-agent injection provides optimal sensitivity for detection of nodal metastases. The acceptable SLN identification and false-negative rates associated with the dual-agent injection technique indicate that this procedure is a suitable alternative to routine axillary dissection across a wide spectrum of surgical practice and hospital environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
313
3
12

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 552 publications
(353 citation statements)
references
References 28 publications
21
313
3
12
Order By: Relevance
“…The overall accuracy and falsenegative rate of SLN biopsy performed in patients with early stage breast cancer have been validated by several large studies and range from 95% to 99% and from 8% to 12%, respectively. [44][45][46] The pathologic status of SLNs is a sensitive and specific predictor of non-SLN status in breast cancer patients. When SLNs are found to be negative for metastasis by thorough pathologic evaluation, complete dissection of axillary lymph nodes and its associated morbidities, including lymphedema and neuropathy, can be obviated.…”
Section: Early Stage Breast Cancermentioning
confidence: 99%
“…The overall accuracy and falsenegative rate of SLN biopsy performed in patients with early stage breast cancer have been validated by several large studies and range from 95% to 99% and from 8% to 12%, respectively. [44][45][46] The pathologic status of SLNs is a sensitive and specific predictor of non-SLN status in breast cancer patients. When SLNs are found to be negative for metastasis by thorough pathologic evaluation, complete dissection of axillary lymph nodes and its associated morbidities, including lymphedema and neuropathy, can be obviated.…”
Section: Early Stage Breast Cancermentioning
confidence: 99%
“…Histological status of the sentinel lymph node is predictive of the status of the regional nodal basin and is used to determine which patients can be spared an axillary dissection [13][14][15]. When multiple sections are cut through histologically negative lymph node(s), approximately 25% of patients otherwise deemed node negative have histologic evidence of micrometastasis [8,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple clinical trials have demonstrated the feasibility and efficacy of lymphatic mapping and sentinel lymph node (SLN) biopsy in patients with operable breast cancer [50][51][52][53][54][55][56]. On average, the rate of false negative SLN biopsy is 8-10%.…”
Section: Sentinel Lymph Node Biopsymentioning
confidence: 99%